Establishing a Microfluidic Tumor Slice Culture Platform to Study Drug Response. Issue 3 (13th March 2023) - Komar, Zofia M.; van Gent, Dik C.; Chakrabarty, Sanjiban
Abstract: Accurate models for tumor biology and prediction of drug responses of individual tumors require novel technology to grow tumor tissue ex vivo to maintain tumor growth characteristics in situ . Models containing only tumor cells, without the stromal components of the tumor, are suboptimal for many purposes and are generally problematic because the cells are passed through extensive culture and selection. Therefore, direct culture of (human) tumors is of considerable interest for basic tumor biology and diagnostic purposes. Microfluidic technologies have been proposed to accurately mimic physiological conditions for tissue growth. Most published systems build tissues from individual cell types in so‐called Organ‐on‐Chip (OoC) cultures. We here describe a novel OoC device for growing tumor specimens. Thin tumor slices are grown in a microfluidic 'chip' that allows precisely controlled in vitro culture conditions. The performance of the OoC device was extensively validated for predicting therapeutic responses in human breast cancer patient‐derived xenograft (PDX) tumor material. The system is amenable to primary tumor material from surgery or biopsies. In addition to using the model to predict and evaluate therapeutic responses, the model can also be used for mechanistic studies of human cancers, such as clonal evolution or immune responses, or to validate new or repurposed (cancer) drugs. The Bi/ond Cancer‐on‐Chip (CoC) device is designed to culture tumor slices and investigate aspects of tumor growth and drug responses. Here, we describe the step‐by‐step process of setting up tumor slice cultures using a Bi/ond CoC device and performing in vitro drug response evaluation. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Establishment of breast cancer tumor slice culture using a microfluidic cancer‐on‐chip platform for chemotherapy testing ex vivo Basic Protocol 2 : Histology and immunohistochemistry‐based analysis of tumor tissue architecture, cell proliferation, and cell death